Antimicrobial Properties of Sonochemically Treated Graphene Oxides Sheets. (2018) - PriyaSwetha, P.D.; Manisha, H.; Abu Bakar, Suriani; Shim, Yoon-Bo; Prasad, K.S.
Abstract: Graphene oxide (GO) has been used as a promising material for antimicrobial surface due to its contact-based antimicrobial activity. The antimicrobial activity of GO was thought to be mediated by physical and chemical interactions when sheets come in direct contact with bacterial cells. Antimicrobial surfaces have important applications in the biomedical field for preventing microbial contamination of medical devices, or in environmental systems where bio-fouling is a major cause of increased operation costs in marine transport, membrane-based water treatment, and heat exchangers. It has been reported that, the antimicrobial activity depends up on the size of GO sheets. Herein, In order to know the accurate assessment of the antimicrobial activity of GO through the suspension assays and surface coatings, we used ultrasonic irradiations to tune the size of GO synthesized through an electrochemical exfoliation method assisted by a surfactant, SDS, in a concentration of 0.01 M to study the antimicrobial activity towards a gram-positive bacteria, Enterococcusfaecalis (cocci) and, a gram- negative bacteria, Escherichia coli (rod-shaped). It has been found that, the ultrasonication time has an effect on the introduction of edge-plane sites on the GO sheets, and their effect on the antimicrobial activity.